KNOWLEDGE RELATIONSHIP WITH THE IMPLEMENTATION OF TT WUS IMMUNIZATION AT PADANGMATINGGI HEALTH CENTER PADANGSIDIMPUAN CITY: IMPLEMENTATION OF TT WUS IMMUNIZATION - Normayanti Rambe (Science Midwifery, 2022)
Tetanus Toxoid (TT) immunization coverage in Women of Childbearing Age (WUS) at the Padangmatinggi Puskemas padangsidimpuan city in 2021 amounted to 0.5% but in fact, the target achieved was not by the national target of 80%. The purpose of the research is to find out the relationship of knowledge with the implementation of TT WUS immunization at the Padangmatinggi Health Center in Padangsidimpuan City. The type of research used is quantitative research with a cross-sectional design. The research population is all wus who are married in the working area of Padangmatinggi Health Center padangsidimpuan city amounted to 305 people with a sample of 75 people. Data analysis using the Chi-Square test. The results showed a knowledge related to the implementation of TT WUS immunization at the Padangmatinggi Health Center with a p-value of 0.001 (< 0.05). It is recommended to health workers to hold socialization about immunization in women of childbearing age and provide motivation to get TT immunization to prevent tetanus disease and consideration to the Padangsidimpuan City Health Office in determining policies and input materials in planning to improve the quality of health services in the TT WUS immunization program.